The Influence of Profit Sharing, Promotion, and Service on Members' Decision-Making in Working Capital Financing at BMT Istiqlal with Company Image as an Intervening Variable - Arzaq, Ahmad Yusril; Kholidah, Nur (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research seeks to examine how profit-sharing, promotional activities, and service quality affect decisions regarding working capital financing at BMT Istiqlal Pekalongan, with corporate image as an intervening variable. The background of this study is based on the strategic role of BMT in providing sharia-based financing for business actors, amid challenges to public image and trust due to external conditions in the sharia microfinance industry. The study employs a quantitative method using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach on 100 respondents who are financing customers. The analysis findings indicate that profit sharing has a significant positive effect on customer decisions and corporate image; promotion has a positive but insignificant effect on customer decisions and corporate image; service has a negative and insignificant effect on customer decisions, but a significant positive effect on corporate image. Company image was found to have a significant positive effect on customer decisions and significantly mediated the effect of service on customer decisions, but did not mediate the effects of profit sharing or promotion. These findings indicate the importance of strengthening a fair profit-sharing system, providing quality service, and implementing consistent promotional strategies to enhance trust and financing decisions at BMT Istiqlal.